Induction of labour and its outcome in a Teaching Hospital - Rathnayake, R.W.M.D.S (My University, 2008)
The leading indications for IOL were past dates 45.8 percent ( 2003) and 4 percent ( 2006) pre labour rupture of memberanes 28.2 percent ( 2003) and 35.4 percent ( 2006). Success vaginal deliveries showed a possible increase from 84.7 percent in 2003 to 90.4 percent in 2006 and failed inductions showed a possible reduction from 3.8 percent in 2003 to 2.2 percent in 2006. Mean induction delivery interval for successful vaginal deliveries varied from 343 minutes ( 95 percent CI 333-370) in 2003 to 318 minutes (95 percent CI 307-327) in 2006. After the adoption of the new guideline and Oxytocin infusion protocol in 2006 IOL and its outcome have improved in the Univeristy Obstetric Unit, Galle.